Organic Thin Films Deposited by Matrix-Assisted Pulsed Laser Evaporation (MAPLE) for Photovoltaic Cell Applications: A Review - Marcela Socol (MDPI AG, 2021)
Human society’s demand for energy has increased faster in the last few decades due to the world’s population growth and economy development. Solar power can be a part of a sustainable solution to this world’s energy need, taking into account that the cost of the renewable energy recently dropped owed to the remarkable progress achieved in the solar panels field. Thus, this inexhaustible source of energy can produce cheap and clean energy with a beneficial impact on the climate change. The considerable potential of the organic photovoltaic (OPV) cells was recently emphasized, with efficiencies exceeding 18% being achieved for OPV devices with various architectures. The challenges regarding the improvement in the OPV performance consist of the selection of the adequate raw organic compounds and manufacturing techniques, both strongly influencing the electrical parameters of the fabricated OPV devices. At the laboratory level, the solution-based techniques are used in the preparation of the active films based on polymers, while the vacuum evaporation is usually involved in the deposition of small molecule organic compounds. The major breakthrough in the OPV field was the implementation of the bulk heterojunction concept but the deposition of mixed films from the same solvent is not always possible. Therefore, this review provides a survey on the development attained in the deposition of organic layers based on small molecules compounds, oligomers and polymers using matrix-assisted pulsed laser evaporation (MAPLE)-based deposition techniques (MAPLE, RIR-MAPLE and emulsion-based RIR-MAPLE). An overview of the influence of various experimental parameters involved in these laser deposition methods on the properties of the fabricated layers is given in order to identify, in the forthcoming years, new strategies for enhancing the OPV cells performance.